Access to weight reduction interventions for overweight and obese patients in UK primary care: population-based cohort study - Martin C Gulliford; A Toby Prevost; Helen P Booth (BMJ Open)
Objectives To investigate access to weight management interventions for overweight and obese patients in primary care.Setting UK primary care electronic health records.Participants A cohort of 91 413 overweight and obese patients aged 30–100 years was sampled from the Clinical Practice Research Datalink (CPRD). Patients with body mass index (BMI) values ≥25 kg/m2 recorded between 2005 and 2012 were included. BMI values were categorised using WHO criteria.Interventions Interventions for body weight management, including advice, referrals and prescription of antiobesity drugs, were evaluated.Primary and secondary outcome measures The rate of body weight management interventions and time to intervention were the main outcomes.Results Data were analysed for 91 413 patients, mean age 56 years, including 55 094 (60%) overweight and 36 319 (40%) obese, including 4099 (5%) with morbid obesity. During the study period, 90% of overweight patients had no weight management intervention recorded. Intervention was more frequent among obese patients, but 59% of patients with morbid obesity had no intervention recorded. Rates of intervention increased with BMI category. In morbid obesity, rates of intervention per 1000 patient years were: advice, 60.2 (95% CI 51.8 to 70.4); referral, 75.7 (95% CI 69.5 to 82.6) and antiobesity drugs 89.9 (95% CI 85.0 to 95.2). Weight management interventions were more often accessed by women, older patients, those with comorbidity and those in deprivation. Follow-up of body weight subsequent to interventions was infrequent.Conclusions Limited evidence of weight management interventions in primary care electronic health records may result from poor recording of advice given, but may indicate a lack of patient access to appropriate body weight management interventions in primary care.